Strategies for Fostering Tilawatil Al-Qur'an in Developing the Quality of Community Qur'an Reading in the Babqah Sikah Institution - Halimatun Hada Wiyah; Hasrian Rudi Setiawan (Journal of General Education and Humanities, 2026)
Limited accuracy in tajwid, improper articulation of makharijul huruf, and weak mastery of Qur’anic recitation melody remain persistent problems among community learners, indicating the need for structured and continuous tilawah coaching. This study aims to analyse the coaching strategies used to foster Qur’anic tilawah, describe their implementation process, and examine their role in improving the quality of Qur’an recitation among the community at the BABQAH SIKAH Institution, North Sumatra. This research employed a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving instructors, administrators, and community participants. Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques. The results show that tilawah coaching is implemented through staged instruction, intensive mentoring, practical recitation exercises, and periodic evaluation. These strategies contribute positively to improving tajwid accuracy, clarity of letter articulation, and mastery of recitation melody. The effectiveness of the program is supported by methodological consistency, instructor competence, and active community participation. Overall, systematic and sustainable tilawah coaching strategies play a significant role in enhancing the quality of Qur'an recitation at the community level.